Bio-concentration of vinasse from the alcoholic fermentation of sugar cane molasses - Navarro, Antonio Roberto (2000)
A concentration-incineration process of vinasse has been in use for several years in order to deal with pollution resulting from the industrial production of ethanol by fermentation and distillation. However, as vinasse concentration has a high energy demand, a bio-concentration method with no energy consumption is reported in this paper. Vinasses was used instead of water in the preparation of the fermentation medium and repeatedly recycled. A final solid concentration of 24% dry matter was produced, an amount that positively modifies the energy balance of the concentration-incineration process. A decrease of 66% in nutrients addition, 46.2% in fresh water and 50% in sulfuric acid requirement was achieved together with an improvement in the efficiency of the fermentation. The final vinasse had a significant amount of non-volatile by-products of commercial importance such as glycerol. A mathematical model is proposed for the prediction of the final solids concentration in vinasse under various working conditions. Copyright (C) 2000 Elsevier Science Ltd.